Evaluación de la calidad de energía eléctrica del edificio matriz del municipio de Ambato - Quilumba Palate, Byron Fabián (2022)
The electrical system installed in large-scale buildings is affected by linear and non-linear charges, which are the electrical and electronic devices that companies, institutions, buildings, among others, have to carry out their work functions, these devices work constantly during the working day from 8:00 a.m. to 4:30 p.m. The set of these elements generates disturbances in the sinusoidal wave and in turn causes deterioration in the quality of electrical energy of the "MATRIX BUILDING OF THE MUNICIPALITY OF AMBATO". The electrical system that tends to be most affected is the low-voltage system coupled to the secondary of the existing 250 kVA transformer. which feeds all the departments of the building. Through field research, I collect a database on the increase in installed load, in lighting systems, special systems, power systems, among others. Through the information base delivered to the student being the "Energy analysis report, the monthly energy consumption corresponding to the years 2019-2020-2021-2022, and the single-line drawings", electrical parameters of power, voltage , power factor, percentage of total and individual harmonics for both voltage and current for the evaluation of electrical power quality. Subsequently, the electrical disturbances obtained with the ETAP program were analyzed, and comparisons were made with the limits established by the regulations: IEEE 519, ARCERNNR 002/20. Using ETAP 19.0.1 software. Finally, solutions were proposed to size new conductors that help reduce losses and voltage drop, the design of an active filter to mitigate harmonics; all this in order to improve the performance of the building to be evaluated.